2016
DOI: 10.1159/000450999
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of HER-2 and p53 Expression in Gallbladder Carcinoma in North Indian Patients

Abstract: Background/Objective: Proto-oncogenes (HER-2) and tumor suppressor genes (p53) are commonly deregulated in gallbladder cancer (GBC). Available literature discloses skewed data from endemic Asian countries, especially north India. This study evaluates the prognostic significance of HER-2 and p53 in GBC patients from two major hospitals. Methods: Sixty resectable tumor and control specimens were prospectively collected from December 2012 to January 2016. Immunohistochemical staining was done using monoclonal ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In addition to the well-known pathological prognostic factors, many molecular features associated with GBC pathogenesis have been proposed as potential biomarkers that might help stratify patients with GBC. Thus, overexpression of p53 [89][90][91], mutations in KRAS [92], amplification of HER2/neu [91,93], overexpression of EGFR [94,95], among other potential molecular prognostic factors such as microRNAs (recently reviewed by Montalvo-Jave et al [5]) have been associated with worse prognosis. Most potential markers have been evaluated in formalin-fixed paraffin-embedded (FFPE) cancer biopsy sections by immunohistochemical analysis, but there are also promising candidates based on RNA/DNA and serum protein detection.…”
Section: Molecular Prognostic Biomarkersmentioning
confidence: 99%
“…In addition to the well-known pathological prognostic factors, many molecular features associated with GBC pathogenesis have been proposed as potential biomarkers that might help stratify patients with GBC. Thus, overexpression of p53 [89][90][91], mutations in KRAS [92], amplification of HER2/neu [91,93], overexpression of EGFR [94,95], among other potential molecular prognostic factors such as microRNAs (recently reviewed by Montalvo-Jave et al [5]) have been associated with worse prognosis. Most potential markers have been evaluated in formalin-fixed paraffin-embedded (FFPE) cancer biopsy sections by immunohistochemical analysis, but there are also promising candidates based on RNA/DNA and serum protein detection.…”
Section: Molecular Prognostic Biomarkersmentioning
confidence: 99%
“…Aberrant HER family signaling may be important in the development and progression of GBC 15,20 . Some studies reported adverse prognostic impact of HER2 expression 16,[23][24][25][26]43 , but others, including ours, did not show such correlation 27,44 . A few studies have investigated anti-HER2 therapy in advanced GBC [45][46][47][48][49] .…”
Section: Discussionmentioning
confidence: 52%
“…Singh et al also found similar results in their study on gall bladder carcinoma. 13 Ashai et al studied the HER2/neu expression in correlation to advanced tumour stage of gall bladder carcinoma and showed that 46% cases were score 1+, 23% were score 2+, 9% cases were 3+ and 19% cases were negative. 14 We also evaluated HER-2/neu expression in gall bladder carcinoma and found similar results.…”
Section: Discussionmentioning
confidence: 99%